Why is the Rail Share of US Freight Traffic So Low?. (1st May 2014) - Boyer, Kenneth
American railroads carry a trivial share of most intermediate and finished products. This paper argues that the vertically integrated structure of the US railroad industry contributes to the reluctance to invest in rail-based distribution systems for finished products and parts. Encouraging contract and private carriage on existing rail networks would enhance long-run economic efficiency. Congestion on key routes will likely permit a financially viable competitive rail industry in which congestion tolls replace the appropriation of shipper profits as the key element of rail pricing. Liberalisation of US rail policy should be completed through permitting second-sourcing of rail services.